PENERAPAN MODEL PROYEK DAN BERKARYA DALAM PEMBELAJARAN SENI BUDAYA DAN KETERAMPILAN UNTUK MENINGKATKAN KREATIVITAS DAN POTENSI BAKAT SENI SISWA KELAS 3 MI DARUL ULUM 02 KUDUS - Alieffia Syaikhoh; Shoffi Aulia Arinsya; Shyfa Natasya Anggraeni; Via Al Barrotuttaqiyah; Rakanita Dyah Ayu Kinesti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The implementation of Project Based Learning (PJBL) in Cultural Arts and Skills learning at MI Darul Ulum 02 Kudus aims to overcome student boredom with conventional methods and enhance creativity and artistic talent potential. This qualitative descriptive study involved 33 third-grade students, employing observation, interviews, and documentation for data collection. PJBL was applied through stages of preparing students and lesson plans, executing the project-based activities including comic creation in groups, monitoring progress, and reflecting on the outcomes. Results indicate increased student engagement, collaboration, and creativity, with the comic project serving effectively to develop artistic skills and foster responsibility. This study confirms that PJBL enhances learning quality by making art education more meaningful and motivating for elementary students.